2016
DOI: 10.22161/ijeab/1.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arsenic in germination, growth and biochemistry of Rice (Oryza sativa)

Abstract: Abstract-Arsenic is a highly toxic metalloid element and occurs in many minerals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…7d). Biswas et al (2016) reported that exposure to As in two rice cultivars, at 4 mg L − 1 , decreased total protein content down to 48.56% and 68.34%. Apparently, when trace metal concentrations are high, higher generation of ROS and therefore greater oxidative stress is observed (Gupta et al 2009) which can cause the reduction in proteins as a result of a greater oxidative damage due to part of the trace elements (Sanal et al 2014).…”
Section: Antioxidant Activity Of Enzymes and Non-enzymatic Compoundsmentioning
confidence: 99%
“…7d). Biswas et al (2016) reported that exposure to As in two rice cultivars, at 4 mg L − 1 , decreased total protein content down to 48.56% and 68.34%. Apparently, when trace metal concentrations are high, higher generation of ROS and therefore greater oxidative stress is observed (Gupta et al 2009) which can cause the reduction in proteins as a result of a greater oxidative damage due to part of the trace elements (Sanal et al 2014).…”
Section: Antioxidant Activity Of Enzymes and Non-enzymatic Compoundsmentioning
confidence: 99%
“…7). Biswas et al, [14] reported that the vigour index exhibits a direct decrease when the concentration of sodium arsenate is increased since it depends on root length, shoot length, and germination percentage [14]. This result was in line with study conducted by Baruah et al, [13], the results of the experiment revealed that the seedlings treated with different concentration of different heavy metals showed the highest reduction (83.4%) in vigour index in 175 mg L -1 of copper (Cu) in wheat followed by 220 mg L -1 of lead (Pb) in pea (79.2%) and 220 mg L -1 (Cd) of cadmium in wheat (78.8%) [13].…”
Section: Seedling Vigour Indexmentioning
confidence: 99%
“…The root length might have a relatively strong suppressive effect than that of the shoot length. Biswas et al, [14] reported that trivalent (As III) and pentavalent (As V) arsenic are accumulated by plants. These forms interfere with phosphate in various metabolic pathways, and interact with sulfhydryl groups on proteins.…”
Section: Root and Shoot Lengthmentioning
confidence: 99%
See 2 more Smart Citations